Geometrical control of pure spin current induced domain wall depinning. (12th January 2017) - Pfeiffer, A; Reeve, R M; Voto, M; Savero-Torres, W; Richter, N; Vila, L; Attané, J P; Lopez-Diaz, L; Kläui, Mathias
Abstract: We investigate the pure spin-current assisted depinning of magnetic domain walls in half ring based Py/Al lateral spin valve structures. Our optimized geometry incorporating a patterned notch in the detector electrode, directly below the Al spin conduit, provides a tailored pinning potential for a transverse domain wall and allows for a precise control over the magnetization configuration and as a result the domain wall pinning. Due to the patterned notch, we are able to study the depinning field as a function of the applied external field for certain applied current densities and observe a clear asymmetry for the two opposite field directions. Micromagnetic simulations show that this can be explained by the asymmetry of the pinning potential. By direct comparison of the calculated efficiencies for different external field and spin current directions, we are able to disentangle the different contributions from the spin transfer torque, Joule heating and the Oersted field. The observed high efficiency of the pure spin current induced spin transfer torque allows for a complete depinning of the domain wall at zero external field for a charge current density of 6 ⋅ 10 11 A m −2, which is attributed to the optimal control of the position of the domain wall.